Sylt Roads Meroplankton time series at List, Ferry Terminal station and Station 1 - Matthias Strasser; Petra Kadel; Ragnhild Asmus; Johannes J Rick; Karen Helen Wiltshire (PANGAEA, 2022)
In order to monitor long-term variability in or eventual change of the planktonic community a quantitative analysis of meroplankton is ongoing since 1996 in the Sylt-Rømø Bight, a region of high ecological importance within the Marine Protect Area National Park Schleswig Holsteinisches Wattenmeer. Since 2014 the sampling is tightly linked to the LTER Sylt Roads time series thus enabling the coupling of species occurrence to the respective hydrochemical and physical conditions in the water column.